The influence of risk diversification on the early exercise of employee stock options by executive officers - Hemmer, Thomas; Matsunaga, Steve; Shevlin, Terry (Journal of Accounting and Economics, 1996)
This paper examines the exercise of employee stock options (ESOs) by executive officers. We document a positive relation between the variance of ESO returns and the remaining life of the option at exercise, and show that the strength of the relation is reduced by the extent the firm hedges the returns on the ESO. We thus provide empirical evidence of a link between an ESO's expected term and its investment risk to the executive, and document that some firms provide a hedge against option risk.